PENGARUH PEMBERIAN TERAPI BERMAIN MEWARNAI GAMBAR TERHADAP PENURUNAN TINGKATKECEMASAN ANAK PRASEKOLAH YANG RAWAT INAP (Studi Experimental di Ruang Nusa IndahRumah Sakit Umum Daerah Pare Tahun 2010) - Agustina, Emi; Puspita, Artie (Akademi Keperawatan Pamenang, 2010)
Anxiety is one of the reactions of children having inpatient treatment in a hospital. Ifunrelieved, it can makethem uncooperative during the treatment process. The objectives of thisstudy wasto know the effect of Playing therapy by colouring picture on alleviating anxieties ofpreschool-age children undergoing inpatient treatment in Nusa Indah Ward of Kediri PublicHospital,Pare.Research method used in the research was pre-experimental research, bypre and posttreatment. The research employs 8 of all preschool-age children undergoing inpatient treatment inNusa IndahWardof Pare Regional Public Hospital from March 19, 2010 to April 19, 2010 as asample. These data were processed by comparing the anxiety scale before the treatment with it afterthe treatment by Hamilton Anxiety Rating Scale, and analyzing data by Cross Tabulating andWilcoxons test.The research concludes that before the treatment 62,5% of all respondents (5 respondents)are on small anxiety scale and 37,5% of them (3 respondents) are on moderate anxiety scale;meanwhile, after the treatment 87,5% of all respondents (7 respondents) do not feel anxieties and12,5% of them (1 respondent) are on small anxiety scale.This means that the playing therapy by colouring a picture is proper to be an alternativetherapy method to use in the hospital to ease preschool-age childrens anxieties when receivinginpatient treatment